Constraint of Different Knee Implant Designs Under Anterior–Posterior Shear Forces and Internal–External Rotation Moments in Human Cadaveric Knees - Saskia A. Brendle; Sven Krueger; Joachim Grifka; Peter E. Müller; William M. Mihalko; Berna Richter; Thomas M. Grupp (Bioengineering)
Instability remains one of the most common indications for revision after total knee arthroplasty. To gain a better understanding of how an implant will perform in vivo and support surgeons in selecting the most appropriate implant design for an individual patient, it is crucial to evaluate the implant constraint within clinically relevant ligament and boundary conditions. Therefore, this study investigated the constraint of three different implant designs (symmetrical implants with and without a post-cam mechanism and an asymmetrical medial-stabilized implant) under anterior–posterior shear forces and internal–external rotation moments at different flexion angles in human cadaveric knees using a six-degrees-of-freedom joint motion simulator. Both symmetrical designs showed no significant differences between the anterior–posterior range of motion of the medial and lateral condyles. In contrast, the medial-stabilized implant exhibited less anterior–posterior translation medially than laterally, without constraining the medial condyle to a fixed position. Furthermore, the post-cam implant design showed a significantly more posterior position of the femoral condyles in flexion compared to the other designs. The results show that despite the differences in ligament situations and individual implant positioning, specific characteristics of each implant design can be identified, reflecting the different geometries of the implant components.